ANALISA AKAD HUTANG PIUTANG YANG DITERAPKAN PADA BAITUL MAAL WA TAMWIL (BMT) MAKMUR MANDIRI PERIODE TAHUN 2019-2021 - Anwar, Syaiful; Baehaqi, B; Sulistyowati, S (Institut Islam Mamba'ul 'Ulum Surakarta, 2023)
Baitul Maal waa Tamwil (BMT) is indeed a different MFI because it has a business and social side. Regulations related to the existence of BMTs include Law Number 23 of 2011 concerning Zakat Management, Law Number 25 of 1992 concerning Cooperatives and Law Number 1 of 2013 concerning Microfinance Institutions (MFIs), as referred to in the Law concerning the Financial Services Authority, Article 1 paragraph (8) of Law no. 1 of 2013 concerning Microfinance Institutions (MFIs). That is an institution that is independent and free from interference from other parties, which has the functions, duties, regulatory authority, supervision, examination, and investigation as referred to in this Law. Article 1 Paragraph (1) of Law no. 11 of 2011 concerning the Financial Services Authority (OJK). One of these institutions is KSPPS-BMT Makmur Mandiri Sukoharjo. The purpose of this study was to determine the procedures for implementing accounts payable contracts on financing products at KSPPS-BMT Makmur Mandiri. The research method used is descriptive qualitative. Sources of data in the form of interviews, observations, and documentation. The results of the study stated that KSPPS-BMT Makmur Mandiri Sukoharjo already had a financing product, namely the Mudharabah Principle, which was divided into two namely mutlaqah and muqayyaddah. Musharaka Principle. The principle of Wadi'ah is divided into two, namely wadi'ah yad dhamanah and wadi'ah Amanah. The principle of buying and selling, consists of murabahah and ishtisna. Services include wakalah, kafalah and ijarah. The principle of loan or debt, consists of hawalah, rahn and qard.